Performing a task with a friend does not change semantic processes but preparation: a social N400 and CNV event-related potential study - Sinha, Sujata; Chau-Morris, Ashley; Kostova, Milena; Debruille, J. Bruno (Frontiers in Psychology, 2025)
The N400 event-related potential (ERP) indexes the semantic processing of words. Recently, social N400 effects were reported: N400 amplitudes were found to be larger in the presence of a confederate. We tested whether this increase would be even larger in participants with friends (Pwfs). This was not the case: whether the words were coherent, incoherent or equivocal, N400s were not larger in Pwfs than in alones. According to the N400 inhibition hypothesis, the social N400 effects previously reported with confederates could then be due to the automatic sidelining of information that occurs when building a common ground with a stranger. Interestingly, contingent negative variations (CNVs) developed as the words had to be classified at the occurrence of an imperative stimulus that followed. PwFs had larger CNVs than alones, suggesting heightened preparation to this imperative stimulus. Unexpectedly, the larger this effect, the less confident PwFs were in their classifications. Given their higher levels of state anxiety before and after the experiment, it thus seems that the presence of someone else completing the same task, even if it is a friend, induces performance pressure, enhances anxiety and preparation, and diminishes self-confidence.